Evaluating Human-Robot Interaction during a Manipulation Experiment Conducted in Immersive Virtual Reality - Duguleană Mihai; Bărbuceanu Florin Grigorie; Mogan Gheorghe (Springer, 2011)
This paper presents the main highlights of a Human-Robot Interaction (HRI) study conducted during a manipulation experiment performed in Cave Automatic Virtual Environment (CAVE). Our aim is to assess whether using immersive Virtual Reality (VR) for testing material handling scenarios that assume collaboration between robots and humans is a practical alternative to similar real live applications. We focus on measuring variables identified as conclusive for the purpose of this study (such as the percentage of tasks successfully completed, the average time to complete task, the relative distance and motion estimate, presence and relative contact errors) during different manipulation scenarios. We present the experimental setup, the HRI questionnaire and the results analysis. We conclude by listing further research issues.
Keywords: human-robot interaction; immersive virtual reality; CAVE; presence; manipulation